(untitled) (Международный научный журнал «Инженер», 2026)
In Tajikistan’s hot climate, asphalt concrete pavements undergo significant thermal loads causing rutting, plastic deformations, and reduced service life. This study justifies the selection of binders (BND 60/90, PMB 90, PG 70-28, PG 76-22) and aggregate gradations to secure thermal resistance. The methodology covers climatic mapping (98th percentile of 7-day maximum surface temperatures [18]), rutting tests [6]), moisture susceptibility [17]), compactability [7], and binder rheology via MSCR [16, 20]. Results indicate that PMB 90 reduces rut depth by 55–60 % at 60 °C vs. BND 60/90 [13, 14], while PG 76-22 yields 70–75 % reduction [11, 14]. Mixes with PMB also show 18 % [17] and achieve 98 % target density [7]. Cost analysis suggests payback through 5-7-year service-life extension [18, 19]. PMB and PG binders are therefore recommended for Tajikistan’s network.